2007
DOI: 10.1681/asn.2006121318
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-1 Sustains Stem Cell–Mediated Renal Repair

Abstract: In mice with cisplatin-induced acute kidney injury, administration of bone marrow-derived mesenchymal stem cells (MSC) restores renal tubular structure and improves renal function, but the underlying mechanism is unclear. Here, we examined the process of kidney cell repair in co-culture experiments with MSC and cisplatin-injured proximal tubular epithelial cells (PTEC). Exposure of PTEC to cisplatin markedly reduced cell viability at 4 days, but co-culture with MSC provided a protective effect by promoting tub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
245
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(264 citation statements)
references
References 49 publications
14
245
1
4
Order By: Relevance
“…The contribution of MSC to increasing proliferation and/or reducing apoptosis for organ rescue has been broadly shown in vivo for renal epithelial cells 19 and nerve cells 20 as a therapeutic benefit. Moreover, some results obtained in vitro show similar effects of MSC on the regulation of apoptosis and/or proliferation of renal epithelial cells, 21 endothelial cells such as aortic cells, 22 brain microvascular cells 23 and cardiomyocytes. 24 Finally, convincing in vitro results obtained by Parekkadan et al 25 show, on the contrary, that MSC favor the death and reduce the proliferation of resident liver cells, specifically activated stellate cells.…”
Section: Discussionmentioning
confidence: 73%
“…The contribution of MSC to increasing proliferation and/or reducing apoptosis for organ rescue has been broadly shown in vivo for renal epithelial cells 19 and nerve cells 20 as a therapeutic benefit. Moreover, some results obtained in vitro show similar effects of MSC on the regulation of apoptosis and/or proliferation of renal epithelial cells, 21 endothelial cells such as aortic cells, 22 brain microvascular cells 23 and cardiomyocytes. 24 Finally, convincing in vitro results obtained by Parekkadan et al 25 show, on the contrary, that MSC favor the death and reduce the proliferation of resident liver cells, specifically activated stellate cells.…”
Section: Discussionmentioning
confidence: 73%
“…59 In another study it was shown that the renoprotective effect of MSCs was mediated by the mitogenic and pro-survival insulin growth factor-1 (IGF-1) produced by the MSCs. 60 Recently, a vasculotropic effect of infused MSC in the kidney was shown, 61 which may be relevant to SSc.…”
Section: Animal Models Of Tissue Protectionmentioning
confidence: 99%
“…MSCs have been shown to secrete a number of growth factors [41]. Imberti et al [43] suggest that this humoral function results from IGF1, whereas Bi et al [42] attributed it to a combination of HGF, IGF1 and EGF. A recent paper by Togel et al [44] suggests that VEGF is the critical factor in the renoprotection afforded by MSCs.…”
Section: Mesenchymal Stromal Cells (Mscs)mentioning
confidence: 99%